MAP kinase p38α regulates type III interferon (IFN-λ1) gene expression in human monocyte-derived dendritic cells in response to RNA stimulation. Issue 2 (3rd December 2014) - Jiang, Miao; O¨sterlund, Pamela; Fagerlund, Riku; Rios, Diana N; Hoffmann, Alexander; Poranen, Minna M; Bamford, Dennis H; Julkunen, Ilkka
Abstract : p38 α MAPK positively regulates the expression of early IFNgenes after RNA stimulation via a pathway in co-operation withIRF3 and NF- κ B. Abstract: Recognition of viral nucleic acids leads to type I and type III IFN gene expression and activation of host antiviral responses. At present, type III IFN genes are the least well-characterized IFN types. Here, we demonstrate that the p38 MAPK signaling pathway is involved in regulating IFN- λ 1 gene expression in response to various types of RNA molecules in human moDCs. Inhibition of p38 MAPK strongly reduced IFN gene expression, and overexpression of p38 α MAPK enhanced IFN- λ 1 gene expression in RNA-stimulated moDCs. The regulation of IFN gene expression by p38 MAPK signaling was independent of protein synthesis and thus, a direct result of RNA stimulation. Moreover, the RIG-I/MDA5-MAVS-IRF3 pathway was required for p38 α MAPK to up-regulate IFN- λ 1 promoter activation, whereas the MyD88-IRF7 pathway was not needed, and the regulation was not involved directly in IRF7-dependent IFN- α 1 gene expression. The stimulatory effect of p38 α MAPK on IFN- λ 1 mRNA expression in human moDCs did not take place directly via the activating TBK1/IKK ɛ complex, but rather, it occurred through some other parallel pathways. Furthermore, mutations in ISRE and NF- κ B binding sites in the promoter region of the IFN- λ 1 gene led to a significant reduction in p38 α MAPK-mediated IFN responses after RNA stimulation. Altogether, our data suggest that the p38 α MAPK pathway is linked with RLR signaling pathways and regulates the expression of early IFN genes after RNA stimulation cooperatively with IRF3 and NF- κ B to induce antiviral responses further.